Three new species of Sphaerosyllis (Polychaeta, Syllidae) from mangrove habitats in Belize - Russellavid, D. E. (Zoologica Scripta, 1989)
Three new species of Sphaerosyllis Claparède, 1863, S. belizensis, S. longilamina, and S. parvoculata, are described from mangrove and adjacent shallow-water habitats of Twin Cays, Belize.
Kristian Fauchald's Polychaeta DB